MORPHOSYNTACTIC ANALYSIS ON INDONESIAN EFL LEARNERSâ DESCRIPTIVE WRITING - Zainuddin, Zainuddin (Lembaran Ilmu Kependidikan, 2016)
This study is aimed at investigating the morphosyntactic issues in English descriptive writing of EFL learners in Indonesia. Therefore, qualitative data were collected from the studentsâ descriptive writing and analyzed in the morphosyntactic issues that lead to the grammatical errors, which take place in descriptive writing. Furthermore, the technique of collecting data was a documentation technique and the analysis technique used is the descriptive analysis. The findings in this study indicated that the EFL learners in Indonesia did not aware of using âsâ for plural mark and third singular in present tense. Then, they did not aware of using âedâ for regular verb in past and past participle form. Moreover, they did not build sentence according to the syntax structure in English because they followed the Indonesian language sentence structure.